IMPLEMENTASI MODEL DISCOVERY LEARNING PADA SEKOLAH MENENGAH KEJURUAN - Abd Rohman (JUPI (Jurnal Pendidikan Indonesia), 2023)
Vocational High School students have different characteristics from their equivalent education level units. The motivation of SMK students to learn on average wants competence in the world of work so that the application of learning models to SMK students needs appropriate learning adjustments and innovations. This study aims to determine the application of the Discovery Learning model model to improve the learning outcomes of SMK students on productive material. The research method uses Classroom Action Research (PTK) with stages 2 cycles. The application of each cycle includes learning activities including planning, implementing actions, observation and interpretation, analysis and reflection. The subjects of this study were 30 students of class XI RPL SMK 2 Delanggu Kota Mojokerto. From the results of the study, it can be concluded that the application of the Discovery Learning model can improve the learning outcomes of vocational students in productive subjects. The increase in learning outcomes was seen from cycle 1 of the Pretest with an average of 50% while the average Postest was 66.7%. In cycle 2 there was an increase in the average value from 83.3% to 93.3%. The results of the average postest scores in cycles 1 and 2 obtained a very significant increase in average results with an average addition of 26.6% So it can be concluded that the use of the Discovery Learning model can be used in vocational students.